Assessment of Production Performances of Exotic Chickens Under Village Production System in Kembata-Tembaro Zone, Southern Ethiopia - Tadesse, Feleke; Ersino, Alemu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The current study was carried out between July 2019 and October 2021 in the districts of Doyogena, Hadero- Tunto (HT), and Angecha of kembata-Tembaro (KT) Zone, Southern Ethiopia, with the aim of assessing management practices and production performance of various exotic chickens under village production system. Based on the possibility for distributing exotic chicken, the districts were deliberately selected. A random selection of nine kebeles was made. Data from a household survey were gathered utilizing a semi-structured questionnaire and file monitoring. To evaluate the data quantitatively, descriptive statistics were employed. For the purpose of strengthening data from the household survey, information from focus groups and individual observations was qualitatively evaluated. The study found out that, the chicken house was constricted 60.4% of the respondents share with people, 20.4% separate with animals and 19.2% constricted separate chicken house. The main feed supplements used for chicken were maize and wheat grains (55.6%), industrial by products (15.2%) and kitchen waste (29.2%). The respondents were provided water as free access (32.2%), in the morning and evening (30%) and provided only in the morning (37.8%). About (78.9%) of the respondents did not used vaccine to their chicken against different diseases. The average mean (60.4%) and (70.2%) of the respondents had good market access to buy chicken production inputs and to sell eggs and chicken, respectively. The breed (BB) was superior for number of egg/year (221.47±12.8) than (SSB) breed (202.91±16.15) and (PK)breed (184.29±5.65); whereas (PK)breed was superior for average age at first egg lying (155±0.94) than (SSB) breed (176.92±0.49) and (BB)breed (168.21±2.78). Diseases and feed shortage were major constraints in the study areas. The overall results of the present study reveal that the majority of the respondents were not used separate chicken housing system and the main feed resources used for their chicken was obtained from grains. Disease and feed problems were the first and the second constraint of exotic chicken production in the study areas. The overall finding indicate that the performance of exotic chicken under farmers’ management condition (BB) breed had better egg production performance than (SSB) and (PK) breeds; whereas (PK)breed was reach better sexual maturity at first egg laying than (SSB) and (BB)breeds in the study areas. However, the performance of the three breeds in the study areas was lower than other findings on similar exotic chicken. The attention given to exotic chicken, particularly in supplementary feeding, health care and housing practices was very low in the study areas. Hence, better housing system, improving the health of chicken, practicing supplementary feeding could increase the productivity.